Chronic low-grade inflammation, lipid risk factors and mortality in functionally dependent elderly - Vasović Olga; Trifunović Danijela; Despotović Nebojša; Milošević Dragoslav P. (Vojnosanitetski Pregled)
Background/Aim. It has been proved that a highly sensitive C-reactive protein (hsCRP) can be used as an established marker of chronic inflammation for cardiovascular risk assessment. Since mean values of both low-density cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) decrease during aging, the knowledge that increased hsCRP concentration predicts mortality (Mt) would influence therapy and treatment outcome. The aim of this study was to examine importance of chronic low grade inflammation and its association with lipid risk factors for all-cause Mt in functionally dependent elderly. Methods. The participants of this longitudinal prospective study were 257 functionally dependent elderly aged 65-99 years. Baseline measurements: anthropometric measurements, blood pressure, fasting plasma total cholesterol (TC), triglyceride (TG), HDL-C, LDL-C, non- HDL-C, hemoglobin A1c (HbA1c) were recorded and different lipid ratios were calculated. Inflammation was assessed by the levels of white blood cells, fibrinogen and hsCRP. The participants with hsCRP grater than 10 mg/L were excluded from the study. The residual participants (77.4% women) were divided into three groups according to their hsCRP levels: a low (< 1 mg/L, n = 70), average (1 to 3 mg/L, n = 69), and high (3-10 mg/L, n = 69) hsCRP group. Associations of all-cause Mt with different risk factors were examined using logistic regression analysis. Results. The hsCRP level showed a significant positive correlation with waist (r = 0.199, p = 0.004) and hip (r = 0.187, p = 0.007) circumferences, body mass index (r = 0.143, p = 0.040) and serum triglyceride level (r = 0.139, p = 0.045) and significant negative correlation with HDL-C (r = -0.164, p = 0.018). Ratios TC/HDL-C and TG/HDL-C were significantly smaller in the low hsCRP group compared to the average hsCRP group (p = 0.019, p = 0.045, respectively) and without significant differences compared with the high hsCRP group. Two years after the baseline examination 22.1% participants died from all-cause Mt. After adjustment for other risk factors, a TC was significantly associated with all-cause Mt only in high hsCRP group: Odds ratio (OR) = 3.71 (95% confidence interval-CI : 1.09-12.63). Conclusions. In this study a high hsCRP was an important factor to identify functionally dependent elderly at high risk who may have more benefit from agressive lipid lowering treatment.